ANALISIS PENGARUH RASIO PAJAK TANGGUHAN,KEAHLIAN PAJAK, DAN REMUNERASI TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2021-2023 - FIKRIYATUL KHABIBAH; Bambang Widjanarko Susilo; Sukemi Kamto Sudibyo (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of the deferred tax ratio, tax expertise, and remuneration on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2023 period. The data used is secondary data obtained from annual financial reports, with a sample of 30 observations selected using a purposive sampling method. The analysis method used was multiple linear regression with IBM SPSS Statistics version 29, preceded by descriptive statistical tests and classical assumption tests. The results indicate that the deferred tax ratio has a partial negative and significant effect on tax avoidance, with a coefficient of -1.880 and a significance value <0.001. Meanwhile, tax expertise has a coefficient of 0.005 with a significance value of 0.729, and remuneration has a coefficient of -0.092 with a significance value of 0.721, indicating that neither has a significant effect on tax avoidance. Simultaneously, all three variables significantly influence tax avoidance, with a significance value of <0.001 and an adjusted R-square of 0.939, indicating the model's high ability to explain the dependent variable. These results indicate that the deferred tax ratio is an important factor in reflecting a company's level of tax avoidance.